Part 2—Enactivism and Learning to Play Tennis: Modification by Adaptation Enabling Action Spaces and Nonconscious Behavioral Mimicry. (2nd November 2022) - Hopper, Timothy; Rhoades, Jesse Lee
Abstract: The second article (Part 2) builds on the theoretical and contextual foundation developed in paper one by exploring in more depth how to teach tennis based on the use of USTA modified equipment and Tennis Canada's play-practice-play program. Drawing on the enactivist cognitive approach to teaching tennis, this paper shows how tennis players, through participatory sense making processes and non-conscious behavioral mimicry, self-organize their action spaces in relation to affordances in the game environment, including their opponent. Using modification by adaptation games this paper highlights specific examples associated with common tactical concepts of time, space, risk and force that can be used to maximize players' game-based learning.